(3GdHjGf aj YOO Bi GdbQBfs - (3YKeGf Hf SYjO Hf YKeGf, CHh YeQh GdOGfj , GHf GdUjQaj, J (B444 (3g` s
(3ChdgG (B:s
(3bGd CHh YeQh YKeGf GdMeO ddg GdPi NTYJ dg GdCUhGH hbUQJ Yfg GdUaGJ gPG cJGH ai YOO Bi GdbQBf hcdeg hMQhag , heYQaI MehSg hYThQg , hecjg heOfjg s
(3BNQgG (B:s
(3bGd CHh YeQh agPG eHdZ LgOfG ajeG CaQOfG dg cJGHfG gPG hMSHfG Gddg hfYe Gdhcjd Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3cJHJ HQSe GdYGde YHO Gddg Hf SGdes
(3hGdfSNI ebGHdI Ydi fSNI Gdabjg Yaja GdOjf YHO Gddg GdHYOGfi s
(3cJHJ GdYfGhjjf HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdbQGAGJ hGdJLhjOs